2016
DOI: 10.1111/anu.12437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phosphorus levels on growth and body composition of crucian carp, Carassius auratusunder indoor and outdoor experiments

Abstract: Indoor and outdoor experiments were carried out simultaneously to evaluate the effects of dietary phosphorus levels on growth performance and body composition of crucian carp. Monocalcium was used to formulate extruded feed containing available phosphorus (AP) of 1.5 (D1), 4.7 (D2), 6.3 (D3) and 9.0 (D4) g kg À1 . Twelve 500-L recirculating tanks were assigned to four triplicate groups with each tank stocked with 15 juveniles (39.88 AE 0.14 g) for indoor experiment. Twelve polyethylene enclosures were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
4
5
0
Order By: Relevance
“…A comparison of the SGR in tank experiments carried out by Chen et al. () (1.19%–1.23%/day) with that in the present research (0.94%–1.20%/day) found that although the feeding rate was much lower in the present experiment, the fish had an SGR that is equivalent to that observed in the experiment of Chen et al. () when sufficient dietary P was provided.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…A comparison of the SGR in tank experiments carried out by Chen et al. () (1.19%–1.23%/day) with that in the present research (0.94%–1.20%/day) found that although the feeding rate was much lower in the present experiment, the fish had an SGR that is equivalent to that observed in the experiment of Chen et al. () when sufficient dietary P was provided.…”
Section: Discussionsupporting
confidence: 73%
“…() (1.19%–1.23%/day) with that in the present research (0.94%–1.20%/day) found that although the feeding rate was much lower in the present experiment, the fish had an SGR that is equivalent to that observed in the experiment of Chen et al. () when sufficient dietary P was provided. The contradictory results of these two experiments revealed that the effect of dietary P level on growth was highly related to the feeding rate.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations